Piezosurgery prevents brain tissue damage: an experimental study on a new rat model - Pavlíková, G; Foltán, R; Burian, M; Horká, E; Adámek, Svatopluk; Hejčl, A; Hanzelka, T; Sedý, J (International journal of oral and maxillofacial surgery, 2011)
Piezosurgery is a promising meticulous system for bone cutting, based on ultrasound microvibrations. It is thought that the impact of piezosurgery on the integrity of soft tissue is generally low, but it has not been examined critically. The authors undertook an experimental study to evaluate the brain tissue response to skull bone removal using piezosurgery compared with a conventional drilling method. In Wistar male rats, a circular bone window was drilled to the parietal bone using piezosurgery on one side and a conventional bone drill on the other side. The behavioural performance of animals was evaluated using the motor BBB test and sensory plantar test. The brains of animals were evaluated by magnetic resonance imaging (MRI) and histology. The results of MRI showed significantly increased depth and width of the brain lesion in the region of conventional drilling compared with the region where piezosurgery was used. Cresylviolet and NF 160 staining confirmed these findings. There was no significant difference in any of the behavioural tests between the two groups. In conclusion, piezosurgery is a safe method for the performance of osteotomy in close relation to soft tissue, including an extremely injury-sensitive tissue such as brain.
Keywords: astrocyty; mozek; Magnetic Resonance Imaging; barvicí látky; lokomoce; Brain; Intraoperative Complications; piezochirurgie; náhodné rozdělení; Coloring Agents; zvířata; Hindlimb; peroperační komplikace; Oxazines; Rats; magnetická rezonanční tomografie; Behavior, Animal; Motor Activity; Neurofilament Proteins; Time Factors; pohybová aktivita; Thermosensing; oxaziny; chování zvířat; mužské pohlaví; temenní kost; neurofilamentové proteiny; Piezosurgery; Osteotomy; Parietal Bone; Random Allocation; poranění mozku; Rats, Wistar; Astrocytes; časové faktory; Locomotion; krysa rodu Rattus; osteotomie; potkani Wistar; Animals; zadní končetina; vnímání teploty; Brain Injuries; Male